Mindfulness mediates the association between chronotype and depressive symptoms in young adults - Gulin Yatagan Sevim; Tina Yuet Law; Simon L. Evans (PLoS ONE, 2025)
Background Chronotype influences risk of depression, with evening-types at higher risk, although the reasons for this are uncertain. Potential mediating factors include mindfulness, sleep quality, rumination, and alcohol consumption, but research is lacking. Methods We explored the role of these factors in the association between chronotype and depressive symptoms amongst young adults, using cross-sectional data collected from a university student sample (N =  546). Results Evening-types had significantly higher levels of depression symptoms, poorer sleep quality, and lower levels of ‘acting with awareness’ and ‘describing’, as well as higher rumination and alcohol consumption. Mediation analyses demonstrated that the link between chronotype and depression was fully mediated by ‘acting with awareness’, ‘describing’, sleep quality, and alcohol consumption. Limitations Only subjective measures were employed, and due to the cross-sectional design, no causal inferences can be made. Conclusion The mediation results shed light on the crucial role of specific mindfulness facets, sleep, and alcohol consumption for explaining why evening types are at higher risk of depression; findings have import for potential interventions aiming to reduce depression risk amongst young adults in particular.